Treatment Strategies for Ventricular Septal Rupture After Myocardial Infarction: A Single-Center Experience - Ma, Dongliang; Zhang, Zhibiao; Zhang, Shunye; Wang, Zhongchao; Zhang, Gang; Wang, Chongjun; Xi, Jicheng (Frontiers in Cardiovascular Medicine, 2022)
Objective: To analyze treatment strategies, prognosis, and related risk factors of patients with postinfarction ventricular septal rupture, as well as the impact of timing of surgical intervention. Methods: A total of 23 patients diagnosed with postinfarction ventricular septal rupture who were non-selectively admitted to Shanxi Provincial Cardiovascular Hospital between October 2017 and August 2021 were included in this study. The relevant clinical data, operation-related conditions, and follow-up data were summarized for all patients. The Kaplan-Meier method and log-rank test were used for the cumulative incidence of unadjusted mortality in patients with different treatment methods. Multivariate logistic regression was used to evaluate the independent risk factors for in-hospital patient mortality. Results: The mean age of the study patients was 64.43±7.54 years, 12(52.2%) were females. There was a significant difference in terms of postoperative residual shunt between the surgical and interventional closure groups (5.9% vs 100%, respectively; P < 0.001). The overall in-hospital mortality rate was 21.7%; however, even though the surgical group had a lower mortality rate than the interventional closure group, (17.6% vs 33%, respectively), this difference was not statistically significant (P=0.576). Univariate analysis showed that in-hospital survival group patients were significantly younger than in-hospital death group patients (62.50±6.53 vs 71.40±7.37 years, respectively; P=0.016), and that women had a significantly higher in-hospital mortality rate than men (P=0.037). The average postoperative follow-up time was 18.11±13.92 months; as of the end of the study all 14 patients in the surgical group were alive, Two out of four patients survived and two patients died after interventional closure. Univariate analysis showed that interventional closure was a risk factor for long-term death (P <0.05). Conclusion: Surgical operation is the most effective treatment for patients with postinfarction ventricular septal rupture; however, the best timing of the operation should be based on the patient’s condition and comprehensively determined through real-time evaluation and monitoring. We believe that delaying the operation time as much as possible when the patient's condition permits can reduce postoperative mortality. Interventional closure can be used as a supplementary or bridge treatment for surgical procedures.